Current molecular and genetic advances in the retinopathy of prematurity [Prematüre retinopatisinde güncel moleküler ve genetik gelismeler] - (:unkn) unknown (My University, 2013)
Despite significant medical and technological advances, retinopathy of prematurity is one of the major causes of visual loss in childhood in developed countries. Retinopathy of prematurity follows the different patterns of clinical courses at preterm infants with similar clinical features. This suggests genetic factors play role in the etiopathogenesis of the diseases such as environmental factors. Genetic researches on retinopathy of prematurity are usually carried out in animal models of oxygen induced retinopathy, and the use of these models provides a better understanding of the disease. In this article, we aimed to review the molecular factors, genetic mutations and polymorphisms that are thought to play a role in the development of retinopathy of prematurity. Understanding of the molecular mechanism in retinopathy of prematurity is extremely important in the development of new agents for the diagnosis and treatment of disease.
Keywords: Genetic; Molecular factors; Retinopathy of prematurity